2017
DOI: 10.1016/j.ejmech.2016.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine (piplartine) and analogues: Antiproliferative microtubule-destabilising agents

Abstract: Piperlongumine (piplartine, 1) is a small molecule alkaloid that is receiving intense interest due to its antiproliferative and anticancer activities. We investigated the effects of 1 on tubulin and microtubules. Using both an isolated tubulin assay, and a combination of sedimentation and Western blotting, we demonstrated that 1 is a tubulin-destabilising agent. This result was confirmed by immunofluorescence and confocal microscopy, which showed that microtubules in MCF-7 breast cancer cells were depolymerise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…In order to evaluate whether 28 directly binds to tubulin at the colchicine binding site, we carried out a competition assay with N , N ′-ethylene-bis(iodoacetamide) (EBI) in MGC-803 cells as described in a previously published paper 47 . EBI was an alkylating agent that cross-links the Cys239 and the Cys354 residues of β -tubulin involved in the colchicine-binding site, forming a EBI: β -tubulin adduct 48 . The adduct was easily detectable by Western blot as a second immunoreactive β -tubulin band that migrated faster than β -tubulin itself 49 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate whether 28 directly binds to tubulin at the colchicine binding site, we carried out a competition assay with N , N ′-ethylene-bis(iodoacetamide) (EBI) in MGC-803 cells as described in a previously published paper 47 . EBI was an alkylating agent that cross-links the Cys239 and the Cys354 residues of β -tubulin involved in the colchicine-binding site, forming a EBI: β -tubulin adduct 48 . The adduct was easily detectable by Western blot as a second immunoreactive β -tubulin band that migrated faster than β -tubulin itself 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Piplartine is a well characterizated cytotoxic agent, able to induce ROS selectively in different cancer cells, leading to cell death by apoptosis [ 3 18 ]. Many piplartine analogs have been synthesized and evaluated against cancer cells; however, this class of compounds has never been employed as ligand for composition of metal complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that complexes of ruthenium with different ligands can induce cytotoxic activity in micromolar or molar range against several cancer cell lines [ 44 46 ]. Moreover, piplartine is able to kill cancer cells of different histological types, including hematological, colon, melanocyte, lung, breast, central nervous system, pancreatic, nasopharyngeal, osseous, bladder, renal, and prostate in micromolar range [ 10 , 12 , 18 ]. In the present work, both piplartine-containing ruthenium complexes showed cytotoxic activity up to 12 fold higher than metal-free piplartine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worth noting is the pellitorine (occurring in pellitory roots) has been shown to have strong cytotoxic activities against HL60 (Human promyelocytic leukemia strain) and MCT-7 (Brest cancer strain) cell lines, with IC50 values of 13.0 µg/mL and 1.8 µg/mL, respectively [43]. Piplartine and analogues have exhibited potent effects in human breast carcinoma MCF-7 cells, whilst being relatively non-toxic to non-tumorigenic MCF-10a cells [44,45]. Other alkamides, as capsaicin was reported to induce the apoptosis of prostate cancer cell lines [46], while pharnilatin did so for those of skin melanoma, as well as lung, ovary and colon [47].…”
Section: Discussionmentioning
confidence: 99%